Medical assistants and students knowledge and practice rate regarding documentation of care provided to patients from medical discipline aspect, Semnan Medical University, 2000-01 - hassan taheri (Babol University of Medical Sciences, 2003)
Background and Objective: One of the factors that a physician can not defend himself in claims is uncompleted medical files of patients. This study was done to evaluate the knowledge and practice rate of medical assistants and students in Semnan Medical University. Methods: This descriptive and analytical study was performed to study the knowledge and practice rate of 134 medical assistants and students regarding medical documentation of provided care in 2000-2001. A twelve-section questionnaire and a checklist were used after confirming their validity and reliability. Data was gathered by interviewing with assistants and medical chart review. Findings: The results showed that 60% of assistants did not know legal aspects of documentation, 74.8% of them did not know how to use abbreviations in final diagnosis and surgeries. 85.8% didn’t know duration of confirmation of verbal orders. The relationship between knowledge and educational courses was significant (P<0.05). Only 10% completed the medical chart legally. Most of assistants tended to record clinical data. There was a significant relationship between practice, education course and knowledge (P<0.05). Conclusion: According to the results, the knowledge and practice were weak. Process of clinical education must be evaluated in outpatient and inpatient wards.